A Novel Rat Model of Thrombogenicity: Its Use in Evaluation of Prothrombin Complex Concentrates and High Purity Factor IX Concentrates - McLaughlin, L F; Drummond, O; MacGregor, I R (Thrombosis and Haemostasis, 1992)
A non-stasis rodent model of thrombogenicity has been used for dose-ranging studies with a conventional prothrombin complex concentrate (PCC) and to evaluate high purity factor IX concentrates from different manufacturers. Fibrin monomer (soluble fibrin) and fibrinopeptide A (FPA) were monitored before and after infusion of test solution. FPA was found to be the more sensitive and reproducible indicator of thrombogenicity and exhibited a dose-related elevation after infusion of the PCC at doses of between 100–300 IU/kg. In contrast the amounts of FPA generated after 300 IU/kg of the high purity factor IX products were similar to control infusions of albumin.